Optical frequency references in acetylene-filled hollow-core optical fiber and photonic microcells - Wang, Chenchen (Kansas State University, 2015)
Optical frequency references have been widely used in applications such as navigation, remote sensing, and telecommunication industry. For stable frequency references in the near-infrared (NIR), lasers can be locked to narrow absorption features in gases such as acetylene. Currently, most Near NIR references are realized in free space setups. In this thesis, a low-loss hollow-core optical fiber with a diameter of sub millimeters is integrated into the reference setup to provide long interaction lengths between the filling gas and the laser field, also facilitate the optical interaction with low power levels. To make portable NIR reference, gas can be sealed inside the hollow-core fiber, by creating a photonic microcell. This work has demonstrated all-fiber optical frequency references in the Near IR by fabricating and integrating gas sealed photonic microcells in the reference setup. Also, a thoughtful study regarding the lineshape of the fiber-based reference has been accomplished. According the proper modeling of a shift due to lineshape, a correction was applied to our previous absolute frequency measurement of an NIR optical frequency reference. Furthermore, effects of the hollow-core fibers, including mode-dependence frequency shift related to surface modes are explored. In addition, angle splicing techniques, which will improve the performance of the fiber-based frequency reference have been created. Low transmission and return loss angle splices of photonic bandgap fiber, single mode PCF, and large core kagome to SMF-28 are developed and those fibers are demonstrated to be promising for photonic microcell based optical frequency references. Finally, a potentially portable optical metrology system is demonstrated by stabilizing a fiber-laser based frequency comb to an acetylene-filled optical fiber frequency reference. Further work is necessary to fabricate an all-fiber portable optical metrology system with high optical transmission and low molecular contamination.
Keywords: Saturation spectroscopy; Photonic crystal fibers; Fusion splicing; Metrological instrumentation; Optics (0752); Physics (0605)